2014
DOI: 10.2147/ijn.s57926
|View full text |Cite
|
Sign up to set email alerts
|

A 90-day study of subchronic oral toxicity of 20 nm, negatively charged zinc oxide nanoparticles in Sprague Dawley rats

Abstract: Purpose The widespread use of nanoparticles (NPs) in industrial and biomedical applications has prompted growing concern regarding their potential toxicity and impact on human health. This study therefore investigated the subchronic, systemic oral toxicity and no-observed-adverse-effect level (NOAEL) of 20 nm, negatively charged zinc oxide (ZnO SM20(−) ) NPs in Sprague Dawley rats for 90 days. Methods The high-dose NP level was set at 500 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…In vivo studies have revealed the ZnO NPs toxicity on experimental animals. ZnO NPs could affect the normal structure and function of the liver in mice, leading to inflammation and hyperemia in the lung,11 even inducing anemia, stomach lesions, kidney atrophy, and eye damage 12…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies have revealed the ZnO NPs toxicity on experimental animals. ZnO NPs could affect the normal structure and function of the liver in mice, leading to inflammation and hyperemia in the lung,11 even inducing anemia, stomach lesions, kidney atrophy, and eye damage 12…”
Section: Introductionmentioning
confidence: 99%
“…After 24 hrs incubation MTT 5mg/ml was added to the plate and 4 hrs incubation was given. The supernatant was removed and added with DMSO to each well and the readings of absorbance were recorded at 580nm using Synergy/HTX MultiScan reader (BioTek) [3637]. The Lethal dose LD 50 of each primary hits were calculated as mean from experiments in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…(2) As for other substances, NM-induced effects should not be overstated. For example, changes in blood biochemistry or redox status at a single time-point are not necessarily representative of pathophysiological liver toxicity (Baati et al 2016;Park et al 2014).…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Zinc oxide (ZnO) NMs are considered to exhibit relative rapid dissolution that contributes to the toxicity of nano-sized preparations. Oral exposure of negatively charged ZnO NMs (approximately 30 nm) in 5-week-old male and female Sprague-Dawley rats daily for 90 days (125, 250 or 500 mg/ kg) followed by a 14-day recovery period resulted in a dose-dependent accumulation in liver (up to 68.67 ng/g tissue) (Park et al 2014). Analysis of serum biochemistry showed a fall in total serum protein and albumin levels in male mice treated with the higher doses.…”
Section: Introductionmentioning
confidence: 99%